2022
DOI: 10.3390/nu14173460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sarcopenia on Clinical Outcomes in a Cohort of Caucasian Active Crohn’s Disease Patients Undergoing Multidetector CT-Enterography

Abstract: (1) Background: Sarcopenia has a high incidence in Crohn’s disease (CD) with considerable heterogeneity among ethnicities and variable impact on clinical outcomes. Aim: to assess the impact of sarcopenia on clinical outcomes in a cohort of Caucasian patients with active CD undergoing CT-enterography (CTE) for clinical assessment. We further investigated the prevalence of sarcopenia and its predictors. (2) Methods: Caucasian CD patients with moderate–severe clinical activity, who underwent CTE in an emergency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Boparai et al [28] reported that the BMI in CD patients with sarcopenia was lower than in CD patients without sarcopenia, 17.2 ± 4.5 vs. 21.5 ± 3.4, p = 0.001, and so did Nardone et al, 20.3 ± 3.1 vs. 23.3 ± 3.8, p = 0.002, and Ge X et al, 20.2 ± 3.5 vs. 21.3 ± 3.0, p= 0.006 in UC patients, while Nam et al reported that BMI is higher in both CD and UC patients with sarcopenia than in patients without sarcopenia, 20.1 ± 3.3 vs. 19.2 ± 3.3 p < 0.0001, 22.4 ± 3.9 vs. 21.6 ± 2.7, p < 0.0001, with no significant difference between CD and UC in the mean BMI [28,29,34,35,39]. Zhou et al reported that low BMI is associated with adverse outcomes such as the need for intestinal surgery, initiation of anti-TNF therapy, or an escalation of biologic therapy.…”
Section: Assessment Of Sarcopeniamentioning
confidence: 93%
See 1 more Smart Citation
“…Boparai et al [28] reported that the BMI in CD patients with sarcopenia was lower than in CD patients without sarcopenia, 17.2 ± 4.5 vs. 21.5 ± 3.4, p = 0.001, and so did Nardone et al, 20.3 ± 3.1 vs. 23.3 ± 3.8, p = 0.002, and Ge X et al, 20.2 ± 3.5 vs. 21.3 ± 3.0, p= 0.006 in UC patients, while Nam et al reported that BMI is higher in both CD and UC patients with sarcopenia than in patients without sarcopenia, 20.1 ± 3.3 vs. 19.2 ± 3.3 p < 0.0001, 22.4 ± 3.9 vs. 21.6 ± 2.7, p < 0.0001, with no significant difference between CD and UC in the mean BMI [28,29,34,35,39]. Zhou et al reported that low BMI is associated with adverse outcomes such as the need for intestinal surgery, initiation of anti-TNF therapy, or an escalation of biologic therapy.…”
Section: Assessment Of Sarcopeniamentioning
confidence: 93%
“…It reported the characteristics only in subgroups of CD and UC patients, respectively. From a total of 16 articles, 5 articles defined sarcopenia with the aid of the skeletal muscle index (SMI) with different cut-off values [28,29,31,34,35], as seen in Table 2. Data on sarcopenia and its correlation with body composition-BMI, visceral fat (VF), subcutaneous fat (SC)-and VF/SC index, are seen in Table 3.…”
Section: Included Studiesmentioning
confidence: 99%
“…Nardone et al ( 28 ) retrospectively evaluated the presence of sarcopenia in a cohort of 63 CD patients with moderate-to-severe clinical activity who underwent CT enterography. In total, 23.8% of patients presented perianal lesions in this cohort.…”
Section: How To Assess Nutritional Status In Pcd Patients?mentioning
confidence: 99%
“…They detected sarcopenia signs in 68.3% of patients. Sarcopenia was associated with a higher risk of infections within 1 year ( 28 ). Furthermore, myopenia has also been associated with primary non-response to anti-TNF therapy ( 29 ).…”
Section: How To Assess Nutritional Status In Pcd Patients?mentioning
confidence: 99%
“…Sarcopenia is usually an aging-related disorder that results in a loss of muscle mass or function. 14 It is also highly prevalent (26.4%-68.3%) in CD patients [15][16][17][18] due to their chronic inflammation, gut microbiota, impaired protein synthesis, malabsorption and malnutrition, corticoid use, and insufficient physical activity due to fatigue. [19][20][21] Sarcopenia is associated with poorer outcomes, re-hospitalization, higher rates of surgery, and postoperative complications in patients with IBDs.…”
Section: Introductionmentioning
confidence: 99%